The Rambang Manuscript in Javanese Tradition: Sufism, Sectarian Negotiation, and the Making of Tolerant Islam in Indonesia - Abdullah, Muhammad; Rochwulaningsih, Yety; Sulistiyono, Singgih Tri; Puguh, Dhanang Respati; Masruroh, Noor Naelil (Journal of Al-Tamaddun, 2025)
The Rambang manuscript, a mid-nineteenth-century Javanese text written in Javanese and Arabic Pegon script, represents a significant work of Kejawen (Javanism) Islamic literature. This study investigates the manuscript’s articulation of Sunni Sufi thought, influenced by al-Ghazālī, through discussions of divinity, cosmos, and humanity. This study employs textual analysis to examine the Rambang manuscript, focusing on its intellectual content, cultural context, and historical significance. Identifying these values was possible because the Rambang Manuscript has been translated from Javanese and Arabic Pegon into Latin script and simultaneously into Indonesian. Results show that the Rambang Manuscript demonstrates intellectual negotiation between orthodox and heterodox Sufi traditions in Indonesia, particularly Java. It attempts to address sectarian conflicts during the Islamization of Java in the 15th and 16th centuries. The text showcases the adaptation of universal Sufi doctrines to local cultural idioms, reflecting indigenous intellectual sophistication. The Rambang Manuscript provides significant contribution to the making of tolerant Islam in Java, offering an intellectual foundation for moderation, reconciliation, and social harmony. These findings contribute to the broader debates on Southeast Asian Islam, highlighting the historical roots of moderation and tolerance in contemporary Javanese Muslim life.